Pinkalicious and the pirates ebook - Kann, Victoria (I Can Read, Level 1: Pinkalicious., 2018)
Readers can watch Pinkalicious and Peterrific on the funtastic PBS Kids TV series Pinkalicious & Peterrific! #1 New York Times bestselling author Victoria Kann brings young readers a Pinkalicious I Can Read pirate adventure about bravery, creativity, and making unlikely new friends. Pinkalicious and Peter go to the hidden cove to meet their friend Aqua, but the mini-mermaid is nowhere in sight. Instead, they see pirates...ARGHH! Pinkalicious and the Pirates is a Level One I Can Read book, which means it's perfect for children learning to sound out words and sentences.